Kekerasan Yang Dialami Oleh Tokoh Utama Dalam Novel 00.00 Sepasang Luka Yang Berakhir Duka Karya Ameylia Falensia - Vebi Puri Sasmita; Eva Dwi Kurniawan (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
In the study under study is related to the study of fiction, namely a novel where the novel is a type of fiction genre that is written in writing where it has several elements of imagination and also in writing where it has some elements of imagination and is also related to wishful thinking while literary criticism is an analysis related to the analysis that deals with the examination of elements that have errors so that the critique generally focuses on the author's some of the author's confusion in writing so that the literature criticism is the result of evaluating a piece of literature. This review aims to describe and reveal violence against female characters in Ameylia Falensia's Nobel. This research utilizes the psychoanalysis method, namely to find out how the deviation in the character and what causes it. In this scope, the researcher took a study that focuses on one of the literary works entitled focused on one literary work entitled 00.00 a pair of wounds that ended in grief written by Ameylia Falensia that ends with grief written by Ameylia Falensia. The results of this study found that there were several cases of psychological and psychological violence. Where the victims generally get a sense of trauma and fear that can trigger a person to do activities that are not in accordance with a person's activity is not in accordance with his reasoning so that it always ends with murder.